Contractions in human blastocysts correlate with aneuploidy, less implantation and delayed arrival to blastocyst: retrospective study with Time-Lapse incubator - Gazzo, Eduardo (2019)
Objectives:To identify contraction (CT) patterns in human blastocysts using a Time-Lapse incubator and to correlate them with their ploidy status by PGT-A analysis, the time they took to reach blastocyst state, implantation rate and clinical pregnancy rate. Design: Retrospective cohort study. Interventions: From October 2016 through May 2018, 270 patients were evaluated, 912 embryos were cultivated in the Time-Lapse (Embryoscope™, Vitrolife) incubator; 778 of them were tested for aneuploidy using an NGS platform in a reference laboratory. Vitrification was performed according to the result of embryo development and awaiting the NGS result, followed by devitrification and transfer of a single embryo. Blastocyst contractions (CT) were determined using the EmbryoViewer (EmbryoViewer™ drawing tools) in order to obtain area, percentage of contraction and the various types of contractions, and these were compared with the NGS genetic study result. 182 transfers were performed to patients with an average age of 30.4 years, range 24 to 39 years. Finally, we obtained the correlation of implantation rate and clinical pregnancy of euploid embryos transferred in the program of assisted reproduction. Results: Embryos were separated into two groups according to contraction during their development: those that contracted (CT) and those that did not, named “only expanding” (OE). OE embryos were euploid in 58.3%, while 53.6% of CT embryos were aneuploid, with a statistically significant difference (p=0.029), meaning that OE embryos had higher chances of being euploid than CT embryos. Pregnancy rate was also higher in OE embryos (63.1% vs. 46.7% in CT embryos; p=0.012). CT embryos took longer to reach the blastocyst stage compared to OE embryos (p=0.004). Women’s age had no correlation with embryo contraction. Conclusions: In this study, embryos who showed contractions had a higher chance of aneuploidy, a lower implantation rate, and required longer to reach the blastocyst stage. The simple fact of observing contractions in an embryo could be useful to decide to transfer another embryo without contractions. Further studies are necessary to prove these findings.